2021
DOI: 10.3390/foods10071635
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Mango By-Products to Enhance the Nutritional Content of Maize Complementary Porridges

Abstract: Mango by-products are disregarded as waste contributing to greenhouse gas emissions. This study used mango seed and kernel to enhance the nutritional content of maize complementary porridges. Composite maize-based porridges (MBP) were formulated by fortifying maize flour with fine ground mango seed and kernel at different levels (31%, 56%, 81%). The by-products and formulated porridges were characterized for their nutritional composition, mineral content, total phenolic content, and antioxidant capacity. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
5
5
0
Order By: Relevance
“…of Mandha et al (2021) were similar to our study who reported that mango peel and kernel enhance the antioxidant content of maize complementary porridge. The addition of mango seed and mango kernel powders in biscuits was studied by Ashoush and Gadallah (2011), and an increase in the overall phytochemical properties was observed.…”
Section: Phytochemical Analysis Of Multigrain Cookies With Mango Wastesupporting
confidence: 92%
See 1 more Smart Citation
“…of Mandha et al (2021) were similar to our study who reported that mango peel and kernel enhance the antioxidant content of maize complementary porridge. The addition of mango seed and mango kernel powders in biscuits was studied by Ashoush and Gadallah (2011), and an increase in the overall phytochemical properties was observed.…”
Section: Phytochemical Analysis Of Multigrain Cookies With Mango Wastesupporting
confidence: 92%
“…Mango peel is a good source of polyphenols and has antioxidant activity, so as the level or ratio of mango peel powder increases, DPPH assay value also showed significant increasing results. Results of Mandha et al (2021) confirmed our finding who reported that mango peel and kernel enhance the antioxidant content of maize complementary porridge.…”
Section: Phytochemical Analysis Of Multigrain Cookies With Mango Wastesupporting
confidence: 90%
“…This means that a child needs to eat a lot of food in order to meet the nutrient needs because the food is more energy and micronutrient-dilute. The moisture content of the porridges was similar to the findings of Kulwa et al (2015) but lower than that of Mandha et al (2021). High moisture content in food products have also been associated with increased growth of microorganisms, which in turn causes spoilage and low nutritional qualities of the food products (Tapia et al, 2020).…”
Section: Discussionsupporting
confidence: 51%
“…The development of pasta, bakery and confectionary products based on natural ingredients/compounds with antioxidant properties and/or with a reduction of sugars and lipid content is a current trend to obtain new and healthier products. Therefore, the incorporation of F&V by-products is researched such as cookies fortified with purple passion fruit epicarp flour [ 147 ], candies fortified with watermelon by-products [ 148 ], nutritionally enhanced maize complementary porridges with mango seed and kernel [ 149 ], cereal-based foods fortified with by-products from the olive oil industry [ 150 ], and spaghetti enriched by persimmon and other vegetal by-products [ 93 , 151 ], among others.…”
Section: Trends and Challenges For Fruit And Vegetable By-products Application In Food Systemsmentioning
confidence: 99%